The development of continental crust through geological time: the South African case - (:unkn) unknown (My University, 1990)
Nd isotopic compositions and $^{147}$Sm/$^{144}$Nd ratios were measured in fifty-eight South African shales and greywackes with depositional ages ranging from 0.2 to 3.3 b.y. Elements such as the rare earths, which are poorly soluble in water and not fractionated during exogeneous processes, preserve the signature of the original crustal source. The $^{147}$Sm/$^{144}$Nd ratios appear to be approximately constant throughout the time interval sampled. We calculated Nd model ages of crustal differentiation. Knowing that the shales represent a true blend of different continental areas we consider these model ages representative of the mean ages of their primitive continental sources. Then, using the inverse technique developed by Allègre and Rousseau in 1984, we computed a growth curve for the continental crust in South Africa. Two periods of important crustal genesis (Archaean and around 1.5 b.y.) can be compared with the observed geology and with other continental crust growth curves obtained in previous studies in southern Africa and in Australia. The observation of large variations in the MgO content and Ni, Cr, U and Th concentrations between Archaean South African shales and post-Archaean samples compared to the constancy of the147Sm144Nd ratios leads us to propose that the Archaean crust was composed of both granite (70.5%) and a mafic component (29.5%) which could have been komatiite. The small dispersion of $^{147}$Sm/$^{144}$Nd ratios suggests that erosion and sedimentation processes yielded homogeneous Archaean shales. The present-day continental crust is much more heterogeneous, because it has undergone several episodes of recycling. Thus recent shales are characterized by more variable $^{147}$Sm/$^{144}$Nd ratios.
Keywords: African Research